Crystal Ordering of Isotactic Polypropylene and Carbon Nanotube Composites Under Shear Stress - Judith, Robert Michael. (Tufts Archival Research Center, 2005)
CNT/iPP nanocomposites were made from solution of iPP/MWCNT in p-Xylene, at nanotube concentrations of 0.01%, 0.1%, 1.0%, 2.0%, and 5.0%, MWCNT by weight, and then dried to form a powder. The powder was then compression molded into a film. The CNT/iPP composite films were then melted in a Linkham shearing stage, and sheared at 1600C at 1 Hz for 2 seconds. Polarized optical microscopy (POM) shows that after crystallization and subsequent reheating the sample birefringence survives beyond the standard melting temperature of iPP. The crystallized sheared films are then analyzed using differential scanning calorimetry (DSC), microscopic transmission ellipsometry (MTE), and wide angle X-ray scattering (WAXS). WAXS scans show formation of ordered crystals consistent with the monoclinic alpha phase of iPP. MTE scans of the sample immediately after shearing and after crystallization confirm the ordering shown in the WAXS scans. DSC scans show a shift in the crystal melting endotherm to higher temperature with increasing CNT concentrations as well as a smaller second endothermic peak that shifts with CNT concentration. We conclude that CNTs increase the crystal ordering in the sheared samples up to a concentration of 1% CNT by weight, while also causing a small increase in the crystal melting temperature. The CNTs do not appear to have an effect on the crystallinity of the samples.